Al-Makky Wa Al-Madany - Hakmi Hidayat; Risma Nur Firdausi H.P; Almay Datus Sania Afifah; Moch. Fahruzzaman (CV. ITTC INDONESIA, 2024)
The Qur'an is the word of Allah revealed to the ProphetxMuhammad SAW. The Qur'an is an eternal miracle, different from the miracles of the previous Prophets. As we already know,xthe Koran was accepted by Rasulullah SAW within a period of 23 years, that is, something was revealed when the Prophetxwas there in Mecca and some were revealed when the Prophet was in Medina. Therefore in a way It is generally acceptedxthat Islamic scholars divide the Qur'an into two parts: makkiyah and madaniyah. Makkiyah is a revelation revealed to thexProphet Muhammad shallAllahu 'alaihi wa sallam before migrating to Medina. Madaniyah is a revelation that wasxrevealed to the Prophet Muhammad shallAllahu 'alaihi wa sallam after emigrating to Medina.x